2005
DOI: 10.1080/13556210412331284748
|View full text |Cite
|
Sign up to set email alerts
|

Long-Term Gene Expression in the Nucleus Accumbens Following Heroin Administration is Subregion-Specific and Depends on the Nature of Drug Administration

Abstract: Repeated exposure to addictive drugs results in long-lasting neuroadaptations in the brain, especially in the mesocorticolimbic system. Within this system, the nucleus accumbens (NAc) plays a major integrative role. As such, the NAc has been shown to be a target of short- and long-lasting drug-induced neuroadaptations at the levels of neurotransmission and cellular morphology. The long-lasting neuroadaptations might depend critically on alterations in gene expression. Recently, we obtained a set of transcripts… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
30
0
5

Year Published

2006
2006
2012
2012

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 46 publications
(36 citation statements)
references
References 84 publications
1
30
0
5
Order By: Relevance
“…These results are in line with previous studies demonstrating differential neuroadaptations in rats receiving heroin in a response-contingent vs -non-contingent manner (Kuntz et al, 2008;Jacobs et al, 2004;Jacobs et al, 2005), and these data may have particular importance for addiction and pain management fields, respectively. Interestingly, we also found that increases in NAc TacR1 mRNA following repeated (moderate dose) heroin was reduced following non-contingent, escalated-dose heroin exposure, possibly reflecting tolerance-associated changes in the NK1 receptor system.…”
Section: Discussionsupporting
confidence: 82%
“…These results are in line with previous studies demonstrating differential neuroadaptations in rats receiving heroin in a response-contingent vs -non-contingent manner (Kuntz et al, 2008;Jacobs et al, 2004;Jacobs et al, 2005), and these data may have particular importance for addiction and pain management fields, respectively. Interestingly, we also found that increases in NAc TacR1 mRNA following repeated (moderate dose) heroin was reduced following non-contingent, escalated-dose heroin exposure, possibly reflecting tolerance-associated changes in the NK1 receptor system.…”
Section: Discussionsupporting
confidence: 82%
“…Indeed, neurobiological correlates of reward (eg neurotransmitter release in the basal ganglia) are increased after response-contingent drug infusions by a far greater magnitude than by response non-contingent drug infusions (Wilson et al, 1994;Mark et al, 1999;Kimmel et al, 2005;Lecca et al, 2007). In addition, different gene expression, neurochemical, stress system, and behavioral adaptations occur in response to volitional vs nonvolitional drug consumption (Stefanski et al, 1999;Jacobs et al, 2005). Therefore, in addition to effects on experimenter-administered nicotine injections, we also assessed the effects of LY235959 on the threshold lowering induced by intravenously self-administered nicotine infusions.…”
Section: Reward-enhancing and Reinforcing Effects Of Nicotine Requirementioning
confidence: 99%
“…Substantial evidence demonstrates that volitional (actively intended) drug intake produces distinct physiological, biochemical, and behavioral effects when compared with forced drug administration. For example, the response contingency of drug exposure robustly influences gene expression (Jacobs et al, 2002(Jacobs et al, , 2003(Jacobs et al, , 2005, neural activation (Chang et al, 1994;Peoples and West, 1996;Stuber et al, 2005), and resultant extracellular neurochemistry (Di Ciano et al, 1996;Hemby et al, 1997;Jacobs et al, 2003;Lecca et al, 2007;Orejarena et al, 2009;You et al, 2007). With specific regard to nicotine, differential effects of volitional SA vs forced drug administration have been observed on a 4 b 2 nAChR expression (Metaxas et al, 2010), cortical glutamatergic projection activity and plasticity mechanisms in the ventral tegmental area (VTA) (McFarland et al, 2003;You et al, 2007), and plasma corticosterone levels (Donny et al, 2000).…”
Section: Introductionmentioning
confidence: 99%